Improving Household Financial Literacy through Nutriladder Educational Media at the Stunting Locus of Sukabumi City - Rosdiana, Delita Septia; Purnamasari, Laely; Wulan, Anisa Nur (Jurnal Abmas Negeri (JAGRI), 2025)
Stunting is one of the serious nutritional problems that currently has not been resolved. One of the risk factors for stunting is economic factors. The level of household financial management plays an important role in choosing nutritious food for each family member. This community service aims to improve family welfare and reduce the risk of stunting by providing knowledge on financial literacy,. Community service activities were carried out in Sukakarya Village, Sukabumi Regency with a total of 46 housewives attending. The education provided was about household budget management and balanced nutrition knowledge. The methods used were lectures, filling out questionnaires, and Nutriladder educational game. The results showed that 80% of participants did not understand financial literacy and did not have savings or insurance. This education is expected to improve family financial decision-making and support efforts to prevent stunting.